Treinamento olímpico na escola: proposta de implantação - Ramos, Jarlimar Lucas da Silva (2016)
The objective of this work was to use and explore the mathematic olympics questions throughout the school year, taking them as a start point for study of the syllabus, and as a source inspiration to elaboration exercises, tasks, simulations and tests, in order to provide to students a continuous preparation for the olympic competitions in mathematics, increasing their self-confidence and enabling improving their results and performance in mathematic discipline. The implementation of a Mathmatics Olympic Traning Pole (MOTP) in a public school in Serra-ES, was needed to implementation the practice of such methodology